Packaging Techniques and Marketing Strategies in Aglonema Ornamental Plant Business in Langsa City - Hanisah, Hanisah; Indra, Siti Balqies; Ariska, Raja Novi; Fadly, Fahmy; Febri, Suri Purnama; Haser, Teuku Fadlon; Syahriandi, Syahriandi; Radhiah, Radhiah; Harahap, Antoni; Acha, Basyarudin (Eumpang Breuh : Jurnal Pengabdian Masyarakat, 2024)
Ornamental plants are plants that are planted and cared for aesthetic and beauty purposes. Ornamental plants are often used in decorative horticulture, landscaping, and interior design. Algonema is a type of ornamental plant that is popular and often found. Aglaonema has wide, colorful leaves, which often have interesting patterns or patterns. Several varieties of Aglaonema have green leaves with white, red, yellow spots, or a combination of these colors. The high demand for aglonema plants opens up opportunities for producers to commercialize them in and out of the city. However, to achieve the target of marketing outside the city, plant packaging is something that must be considered so that the plants can reach consumers properly and intact. The purpose of this service is to find the right packaging for marketing Aglonema outside the region and determine an efficient marketing strategy to reach consumers and increase marketing. The PKM activities carried out include: mentoring and outreach regarding suitable, inexpensive and safe aglonema packaging techniques for sales outside the region as well as developing a sales strategy to reach a wider range of consumers; business model mapping based on determining target consumers that have been determined by partners; register partners on e-commerce platforms and marketplaces to facilitate the product sales process and reach wider consumers; assistance with e-commerce and marketplace applications to partners; and within a period of 3 months, the service team evaluates the use of e-commerce and marketplaces. After the service is carried out, partners have knowledge about packaging techniques and marketing strategies for aglonema ornamental plants so that partner income increases.